Pustinja zacvete kakor narcisa - Handley, George B. (Poligrafi, 2021)
The Church of Jesus Christ of Latter-day Saints (aka The “Mormon” Church) offers what believers consider to be the restoration of an original Christianity. This essay explores the grounds for a Latter-day Saint restoration of a once-lost ecological wisdom that could make contemporary settlements in the American West more sustainable, especially where Latter-day Saints have established many communities. While Latter-day Saints and many other settlers of the West considered their work to be a kind of fulfillment of Isaiah’s prophecy to make the desert “blossom as a rose” through radical environmental transformation, this essay argues for a more aesthetic and ecologically sensitive response to the native qualities of the desert that need protection or even restoration.
Keywords: Aldo Leopold; Cerkev Jezusa Kristusa svetih iz poslednjih dni; conservation aesthetic; desert; ecology; Ekologija; Filozofija; Mormon Church; Mormonism; Mormonska cerkev; naravovarstvena estetika; puščava; the Church of Jesus Christ of Latter-day Saints; Utah; Varstvo narave; Wallace Stegner